2022
DOI: 10.29333/ejmste/12512
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic reasoning in science education: A literature review

Abstract: There is a growing research interest in mechanistic reasoning (MR) in the field of science education, as this type of reasoning is perceived as an essential thinking skill for science education. This literature review synthesized 60 science education studies on MR published from 2006 to 2021. The findings showed three common aspects of conceptualizations of MR in science education: (1) causality in relation to MR, (2) use of entities and their associated activities, and (3) use of entities at (at least) one sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…In their dimension construct, Zhai et al (2020a) found that 81% of the reviewed studies tapped complex constructs indicating the great potential of ML in assessing such constructs. Since mechanistic reasoning is a complex construct per se (cf., Bachtiar et al, 2022), our review confirms Zhai et al's (2020a) finding. However, in many studies of our sample, there is no evidence that the investigated construct could solely be analyzed by ML.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In their dimension construct, Zhai et al (2020a) found that 81% of the reviewed studies tapped complex constructs indicating the great potential of ML in assessing such constructs. Since mechanistic reasoning is a complex construct per se (cf., Bachtiar et al, 2022), our review confirms Zhai et al's (2020a) finding. However, in many studies of our sample, there is no evidence that the investigated construct could solely be analyzed by ML.…”
Section: Discussionsupporting
confidence: 91%
“…Across all sciences, mechanistic reasoning is a critical thinking skill (Machamer et al, 2000;Glennan, 2002;Russ et al, 2008;Bolger et al, 2012;Illari and Williamson, 2012;Southard et al, 2016;van Mil et al, 2016). However, students experience significant challenges in generating mechanistic explanations in science subjects (cf., Bachtiar et al, 2022). Research in chemistry education has as well documented that these challenges include reasoning about chemical mechanisms in organic (cf., Graulich, 2015;Watts, 2022a, 2022b) or general chemistry (cf., Talanquer, 2009;Sevian and Talanquer, 2014) since many cognitive operations must co-occur.…”
Section: Introductionmentioning
confidence: 99%
“…Highlighted by our literature study (Bachtiar et al, 2022), also reported by other studies (e.g., Andrade et al, 2021; Bachtiar et al, 2021; Wilkerson et al, 2018; Wilkerson‐Jerde et al, 2015), students used MR when reasoning with their own creation of a model of a phenomenon. Given a growing research interest in student‐constructed stop‐motion animations (SMA) as digital explanations that have been shown to support science learning (see Farrokhnia et al, 2020; Hoban, 2020; Nielsen et al, 2022; Paige et al, 2016; Yaseen & Aubusson, 2018), our present study focuses on exploring the contribution of student‐constructed SMA for specifically supporting MR.…”
Section: Introductionsupporting
confidence: 76%
“…The findings in our current study add the knowledge to the field by emphasizing that students' engaging in constructing chunks and sequencing these chunks (by thinking about the transition between the sequential chunks), led students to employ the basic elements of MR, that is, identifying entities and activities of entities. It is precisely these elements that were found to be the most challenging elements that students need to involve in when developing MR (Bachtiar et al, 2022).…”
Section: Line Excerpt Smentioning
confidence: 99%
See 1 more Smart Citation